(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The current research is based on the safety of food and nutrition laws in developing countries. The main objectives of the research such as the importance of the safety of food legislation in developing countries, the elements of a good national food safety system, the barriers, and gaps in the implementation of the safety of food legislation in developing countries, and the importance of the policies and programs for nutrition are discussed. The application of legislation for the safety of food is an essential concern to maintain the quality of food. Several challenges to the safety of food are reduced by the execution of food safety legislation in a developing country.